Forecasting Seizure Freedom After Epilepsy Surgery Assessing Concordance Between Noninvasive and StereoEEG Findings. Issue 1 (31st July 2020) - Uribe San Martin, Reinaldo; Di Giacomo, Roberta; Mai, Roberto; Gozzo, Francesca; Pelliccia, Veronica; Mariani, Valeria; Cardinale, Francesco; Ciampi, Ethel; Onofrj, Marco; Tassi, Laura
Abstract: BACKGROUND: Accurate localization of the probable Epileptogenic Zone (EZ) from presurgical studies is crucial for achieving good prognosis in epilepsy surgery. OBJECTIVE: To evaluate the degree of concordance at a sublobar localization derived from noninvasive studies (video electroencephalography, EEG; magnetic resonance imaging, MRI; 18-fluorodeoxyglucose positron emission tomography FDG-PET, FDG-PET) and EZ estimated by stereoEEG, in forecasting seizure recurrence in a long-term cohort of patients with focal drug-resistant epilepsy. METHODS: We selected patients with a full presurgical evaluation and with postsurgical outcome at least 1 yr after surgery. Multivariate Cox regression analysis for seizure freedom (Engel Ia) was performed. RESULTS: A total of 74 patients were included, 62.2% were in Engel class Ia with a mean follow-up of 2.8 + 2.4 yr after surgery. In the multivariate analysis for Engel Ia vs >Ib, complete resection of the EZ found in stereoEEG (hazard ratio, HR: 0.24, 95%CI: 0.09-0.63, P = .004) and full concordance between FDG-PET and stereoEEG (HR: 0.11, 95%CI: 0.02-0.65, P = .015) portended a more favorable outcome. Most of our results were maintained when analyzing subgroups of patients. CONCLUSION: The degree of concordance between noninvasive studies and stereoEEG may help to forecast the likelihood of cure before performing resective surgery, particularly using a sublobar classification and comparing the affected areas in the FDG-PET with EZ identified with stereoEEG. Graphical Abstract: